Determination of the efficacy of ultrasound-guided bilateral transversus abdominis plane (US-TAP) block in laparoscopic total extraperitoneal (TEP) repair of unilateral hernia surgeries: A randomized controlled trial - Vijayalakshmi Sivapurapu; Sri Vengadesh Gopal; Ashley Solomon (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Bilateral ultrasound-guided transversus abdominis plane (US-TAP) block has been successfully used to provide analgesia for most lower abdominal procedures. Our aim was to determine the efficacy of US-TAP block with levobupivacaine in laparoscopic total extraperitoneal (TEP) repair of unilateral hernia surgeries under general anaesthesia (GA) as compared to no block. Material and Methods: It is prospective randomised controlled study done in a tertiary care centre in South-East Asia. After obtaining Institute Ethics Committee approval and consent, 60 patients of ASA I-II aged between 18 to 80 years were randomized into two groups.After receiving GA, Group TAP - received bilateral US-TAP block with levobupivacaine 0.25% 0.3ml kg-1 on either side whereas, the control group did not receive any block.The time taken to first request for rescue analgesic (T Rescue) by the patient and the Numeric Rating Scale (NRS) at that time point were noted and tramadol 50mg i.v. was administered, followed by 50mg i.m. PRN for 24 h from the time of extubation. The 24 h analgesic requirement was noted in mg kg-1. Results: Results were analysed using SPSS 16 and P < 0.05 was considered significant. T Rescue was significantly longer in the TAP Group (P = 0.02) with lower NRS at time points 24 h (P = 0.02) and 12 h (P = 0.004). Postoperative nausea and vomiting were significantly less in TAP Group (P < 0.001). Conclusion: Bilateral US-TAP block provided better analgesia and side effect profile as compared to no block when administered in laparoscopic TEP repair of hernia surgeries.